Bullying and victimization in early adolescence: Relations to social information processing patterns. Issue 6 (1st July 2013) - Ziv, Yair; Leibovich, Inbal; Shechtman, Zipora
Abstract There is a gap in the literature on the social information processing (SIP) patterns of adolescents exposed to victimization in school. Therefore, we examine the SIP patterns of young adolescents characterized by their teachers and by their own reports as victims, bullies, bullies/victims, and neither bullies nor victims. The 105 adolescents participating in this study were asked to respond to hypothetical social scenarios in which a protagonist is either rebuffed or provoked by peers. The scenarios were ambiguous in nature and thus could have been processed in different ways. Indeed, distinctive processing patterns were found for each of these groups: victims tended to avoid challenging social situations while expecting others to be purposefully hostile or ignoring; bullies tended to interpret others as purposefully hostile and stated their desire to retaliate; bullies/victims showed patterns more similar to those of the bullies than the victims; and those who were neither victims nor bullies tended to view the same challenging social situations as non hostile and more likely to end well for them. We conclude by discussing the theoretical and practical implications of these findings. Aggr. Behav. 39:482–492, 2013. © 2013 Wiley Periodicals, Inc.